The Art of Manufacturing: Overcome control challenges for increasing efficiency in manufacturing using real-world examples - Deshpande, Ninad; Pothukuchi, Sivaram (Packt Publishing, 2023)
Demystify automation and solve control-related problems with the help of real-world products and case studies put together by two industrial automation experts Key Features Real life applications and case studies of automation curated from authors rich experienceOvercome tricky automation and control issues in the manufacturing processImplement automation in manufacturing for higher efficiency and productivity in the industry Book Description Engineering disciplines focus mainly on programming control systems, while the challenges they overcome or their industry applications largely go uncovered, leaving a huge gap between the theory and industry practices. This leads to engineers learning about subjects without actually understanding their purpose and entering the industry needing months of training. The Art of Manufacturing cuts across pedantic theory and reaches practical applications. You’ll begin your learning journey by starting from the product and moving backward to the manufacturing landscape, factories, machines, and finally to the automation and control challenges faced in manufacturing. The book builds on the authors’ valuable on-field experience, providing a detailed view of the manufacturing of real-world products, while simultaneously providing various analogies and references to daily tasks. As you advance through the chapters, you’ll work on interesting control problems and find out how to overcome them in applications. The concluding chapters offer you a sneak peek into the future of automation and factories. By the end of this book, you’ll be able to relate a real-world product with an associated control challenge and discover ways to overcome these challenges. What you will learn Understand the role of machines, factories, and plants in manufacturing a productExplore the manufacturing landscape and its continuous evolutionUse practical applications to mitigate control challenges in manufacturingResolve implementation challenges of various applications in a machineDiscover how humans and automation work together in factoriesFind out how to solve the same control challenge in different waysDiscover links between Industry 3.0, Industry 4.0, digitalization, and lean manufacturing Who this book is for The book will interest an inquisitive student of engineering (electrical, electronics, mechatronics, E&TC) who wishes to explore beyond the classroom textbook content. It will also serve as a teacher’s handbook helping the lecturer bring the flair of industry into the classroom. Moreover, it will be useful for a practicing engineer, with cross-disciplinary knowledge that is needed to manufacture any real product. You must have basic knowledge of electronics, electrical, and mechatronics (engineering).